Islamization of the Southeast Asia : the role of Turks - Kayadibi, Saim (2012)
Recently the dramatic developments of Asian countries, especially China, Malaysia, Japan and India in terms of economic and finance activities brought the idea that the 21st century will be the century of Asia and therefore this region has great potential to be political, economical, and civilizational centre of the world. In that respect the role that Malaysia will play is significantly important for the region and the Muslim ummah. Islamization of the region has to be taken into consideration for long term success. The past experience that Malaysia had, must be used. It’s known that Islamization of the Southeast Asia took more than centuries. Since the religion of Islam is a universal religion, its message conveyed to other part of the world through either Arabs, Turks, Malays or any other Nations who comprehended the inner and outer dimension of the eternal message of the Qur’an which granted them the leadership of the world. In the early years of the thirteenth century, relations between the traditional Islamic heartland and Malay world began to increase. Especially the Turk-Malay relationship has been increased gradually since the beginning of the thirteenth century with the coming of the Rumis (Asian Turks) to the Archipelago and the great period of Islamization in Southeast Asia after the thirteenth century, Islam acquired strong political power in several part of the Malay world. In this paper, especially the Turk-Malay relationship will be investigated which it would take three distinct historical stages: the beginning of the thirteenth century, the pan-Islamic era of Sultan Abdulhamid II, and after the Ottoman Empire was replaced by the Republic of Turkey.